Pengukuran Kinerja Perbankan Menggunakan Kriteria Malcolm Baldrige National Quality Award (Studi Kasus Pada PT. Bank XYZ) - Fakhrina Fahma; Roni Zakaria; Muhammad Hary Sajiwo (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2012)
PT. Bank XYZ is one of a growing bank in Indonesia. At the branch level and business unit, PT. Bank XYZ has been using the financial report or financial statements as a KPI (Key Performance Indicators) in order to conducting performance measurement. Beside the financial report, steps needed to survive the competition and developments in the banking world is equipped with an evaluation of service levels to customers and performance measurement in the company externally. At the external level, performance measurement is considered important because it can figure out how to deal with customers and commitment to listening to customers in the long term market success. This study aims to measure the performance of PT. Bank XYZ so that consistency of performance can be monitored. To know this, carried out using criteria Malcolm Baldrige National Quality Award 2009-2010. One of the selected categories, namely customer focus category. In the measurement of customer focus category is divided into two parts, namely, measurement of performance-related managerial and performance measurement related to the consumer (customer). Measurements relating to Managerial done with interviews and discussions with the leaders (branch manager) PT. Bank XYZ, while associated with consumer (customer) is done by measuring customer satisfaction using a questionnaire based on five dimensions of SERVQUAL. Number of samples to be used as a customer satisfaction questionnaire in this study of 100 respondents who were trading in PT. Bank XYZ. From the survey results revealed that the quality of service PT. Bank XYZ is based on five dimensions of SERVQUAL is expressed either as the average interval between the range 3.4 to 4.19. However, when viewed from the level of customer satisfaction is based on the interests of performance, found that of the five dimensions of quality of existing services, the customer is not satisfied but the approach is quite satisfied with the service at the PT. Bank XYZfor satisfaction scores showed a minus (-). MBNQA criteria for scoring the results of customer focus category has score 54 of the total score of 85 points. Item get customer engagement score of 28, while the voice of the customer items to score 26. These results indicate a good first step in developing a performance measurement in the other six MBNQA criteria.